2020
DOI: 10.1002/tax.12322
|View full text |Cite
|
Sign up to set email alerts
|

IAPT chromosome data 32

Abstract: The research was carried out within the framework of project VI.52.1.2, "Analysis of the intraspecific structure of resource plants Version of Record 1127 TAXON 69 (5) • October 2020: 1126-1132 Marhold & Kuc ˇera (eds.) • IAPT chromosome data 32 in Asian Russia, selection and conservation of the gene pool" (No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Colpodium versicolor is another grass species that has only four chromosomes in its karyotype [12][13][14][15][16]. Based on morphological characters it is suggested that C. versicolor is closely related to Z. biebersteiniana [10].…”
Section: Of 11mentioning
confidence: 99%
“…Colpodium versicolor is another grass species that has only four chromosomes in its karyotype [12][13][14][15][16]. Based on morphological characters it is suggested that C. versicolor is closely related to Z. biebersteiniana [10].…”
Section: Of 11mentioning
confidence: 99%